Pattern of Otolaryngological Diseases among Paediatric Population Attending ENT OPD in a Tertiary Care Centre, Dhaka (Delta Medical College Journal, 2017)
Background: Ear, nose and throat diseases are serious public health problems affecting all age groups. These include problem of hearing, speech, phonation, breathing, swallowing, smell and taste and protection of lower respiratory passage.Objective: There is lack of data on paediatric ENT diseases in our country and their consequences. This study was undertaken to determine the hospital prevalence of ENT diseases among paediatric population.Materials and method: This is an observational study which included 430 children presenting with ENT problem in the Department of ENT OPD, in a Tertiary Care Centre at Dhaka, Bangladesh from January 2013 to December 2013.Results: The current study was conducted among children aged 0-15 years attending ENT OPD with common otolaryngological problems. Prevalence of ENT disease was more common among male children (52.79%) mostly belonging to 0-5 years (male 52.86% and female 42.36%). Vast majority of these children belonged to lower middle class family (52.32%) with inadequacy of basic health care needs. Diseases of the ear (39.75%) were most common followed by throat problems (33.71%) and nasal diseases (26.51%).Conclusion: Otitis media (acute and chronic), rhinitis and tonsillitis were most prevalent ENT disorder among the selected paediatric population. So clinicians should be familiar with these conditions to prevent potential morbidity and to create parental awareness.Delta Med Col J. Jan 2017 5(1): 30-34